Analisis Faktor-Faktor yang Menghambat Perkembangan Bahasa Anak - Della Rahmadani, Nafa; Noviyanti, Silvina; Juliana Dwi Putri, Selsha (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to identify and understand external factors that hinder children's language development, as well as develop effective strategies to overcome them. The research method uses a qualitative descriptive approach, which was chosen because it allows researchers to explain these external factors in depth and detail. The research results reveal that parenting patterns, the order or number of children, the surrounding environment, and social settings are the main external factors that hinder children's language development. In conclusion, implementing appropriate strategies, such as optimizing parenting patterns, paying attention to the order or number of children, creating a supportive learning environment, and adapting to social settings can optimize children's language development, facilitate better communication, and understanding of their social environment.